IMPLEMENTASI ENTERPRISE RESOURCE PLANNING PADA TOKO BUNGA REN FLORIST CO - Scholastica Lewoema; Putri Taqwa Prasetyaningrum (Journal of Computer Science and Technology, 2022)
In this era filled with many digital-based activities, it indirectly encourages business people to move out of their comfort zone. One of them is Ren Florist Co. Flower Shop. Flower Shop Ren Florist Co. is a flower shop engaged in the sale of flowers. Opened in early 2017, Ren Florist Co is already marketing its products online. However, this has not been considered effective, because several work systems such as making billing receipts, cashiers, official websites, employee recruitment processes, and filling out employee databases have not used an adequate ERP system. Therefore, in this study, the application that can overcome the problems that occur is the Odoo ERP application. Odoo is an open-source ERP application that can be accessed through the website, which is suitable for use in new companies so that it can reduce costs for the application development process. The modules developed at Ren Florist Co Flower Shop include the Sales Module, Point of Sale Module, Website Module, Recruitment Module, and Employees Module.